THE IMPLEMENTATION OF THE INSIDE OUTSIDE CIRCLE (IOC) LEARNING MODEL IN AKIDAH AKHLAK SUBJECT TO IMPROVE THE LEARNING ACTIVITIES OF GRADE VII STUDENTS AT SMP NEGERI 1 NOLING - Mesi (PT. Jurnal Center Indonesia Publisher, 2025)
This thesis discusses the implementation of the Inside Outside Circle (IOC) learning model to improve the learning activities of Grade VII-1 students. In the initial condition, students showed low learning activity, as reflected in their behavior during lessons. The purpose of this study is to analyze the implementation of the Inside Outside Circle (IOC) learning model in enhancing the learning activities of Grade VII students at SMP Negeri 1 Noling. This research employed Classroom Action Research (CAR) using the Spencer Kagan model. The study was conducted in two cycles involving 21 students as research subjects. Data collection techniques included observation, teacher observation sheets, student observation sheets, and student activity sheets, which were then analyzed both quantitatively and qualitatively. The findings revealed an increase in the average student learning activity score from 43.40% in Cycle I to 92.15% in Cycle II. This study demonstrates that the implementation of the Inside Outside Circle (IOC) learning model is effective in improving the learning activities of Grade VII students at SMP Negeri 1 Noling.